Temperatura mínima basal, acúmulo de graus-dia, duração do ciclo, componentes de rendimento e estimativa de produtividade para cultivares de trigo - Noreto, Lorena Maia (2018)
The objective of the present study was to determine the minimum basal temperature, growing degree-day and cycle duration, for different phenological stages of wheat development. As well as evaluating the grain yield components and the wheat yield estimation model at different sowing dates and location. The experiments were carried out in the field at COODETEC Research Centers, located in the municipalities of Cascavel and Palotina, in Paraná State. The experimental design used was in randomized blocks in a factorial scheme (7 x 3). The treatments consisted of seven wheat cultivars (CD 108, CD 1104, CD 1440, CD 150, CD 154, CD 1550 e QUARTZO) and three sowing dates for Cascavel (04/22/15, 04/30/15 and 05/21/15) and Palotina (03/31/015, 04/16/15 and 04/27/15), with three repetitions. The variables evaluated were: duration of the periods in days for the intervals of the sowing to the silking and, sowing to the physiological maturation, minimum basal temperature, growing degree-day, number of ears per square meter, number of grains per spike, mass of one thousand grains and grain yield. The reduction in air temperature tends to increase up to 12 days the intervals between sowing and silking, and between sowing and physiological maturation, for both Cascavel and Palotina. For the different cultivars the minimum basal temperature varied from 0°C to 3.7°C for the sowing period to the silking and 5.8°C to 14,1°C for the silking period to the physiological maturation. The thermal requirements for the cultivars reach the reproductive stage (silking), vary from 817 degree-day (CD 108) to 1270 degree-day (QUARTZO). For cultivar CD 108, the sowing period to the ‘physiological maturation was not altered according to the sowing dates in Cascavel. For the other cultivars (CD 1104, CD 1440, CD 150, CD 154, CD 1550 and QUARTZO) there were variations in the sowing period to physiological maturation at different sowing dates. The number of ears per square meter has a greater contribution to increase the grain yield for the cultivars evaluated. The Sowing on 05/21/15 in Cascavel and 04/16/15 in Palotina resulted in grain yield with average of 5391 kg ha-1 and 3409 kg ha-1, respectively. The mathematical model of productivity estimation obtained a performance considered "Good" to estimate the grain yield of cultivars CD 1440 and QUARTZO.